Pola Santri Pesantren Nurul Islam (NURIS) II Jember dalam Penggunaan Facebook sebagai Media Komunikasi: Patterns of Islamic Boarding School Students (NURIS II Jember) in Using Facebook as a Communication Medium - Siti Raudhatul Jannah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2014)
The development of Facebook members in the last five years has been truly phenomenal, with a growth rate of 118% each month. Facebook needed only about five months to reach 150 million members from 170 countries worldwide, using at least 35 languages. The researcher is interested in examining the patterns and responses of Islamic boarding school students, managers, and kiai in accessing and using Facebook sites. This interest is based on the assumption that they have different patterns and attitudes in accessing Facebook sites. The research problem is how the students and managers' patterns and responses in using Facebook sites as a communication medium. This research uses a descriptive qualitative method and collects data through interviews. Perkembangan anggota Facebook dalam lima tahun terakhir sangat fenomenal, mencapai peningkatan sebesar 118% setiap bulan. Facebook hanya membutuhkan waktu sekitar lima bulan untuk mencapai 150 juta anggota dari 170 negara di dunia, dengan menggunakan minimal 35 bahasa. Peneliti tertarik untuk meneliti pola dan respons santri, pengelola, dan kiai dalam mengakses serta menggunakan situs Facebook. Ketertarikan ini didasarkan pada asumsi bahwa mereka memiliki pola dan sikap yang berbeda dalam mengakses situs Facebook. Masalah penelitian ini adalah bagaimana pola dan respons santri serta pengelola dalam menggunakan situs Facebook sebagai media komunikasi. Penelitian ini menggunakan metode kualitatif deskriptif dan mengumpulkan data melalui wawancara.